Utilization of clinical videography technique in the assessment of tear meniscus rising speed - Ithnin, Mohd. Hafidz; Ariffin, Azrin Esmady; Mohd Kamal, Khairidzan (2019)
Purpose: The utilization of clinical videography technique in the assessment of dynamic tear meniscus was not explained thoroughly. This study was conducted to assess the rising speed of tear meniscus using clinical videography technique.